Paediatric unicystic ameloblastoma - A report of 2 cases - Spoorti Kulkarni; Subhalakshmi Sen; Chetana Chandrashekar; Venkadasalapathi Narayanaswamy; Raghu Radhakrishnan (Wolters Kluwer Medknow Publications, 2020)
Unicytic ameloblastoma is a variant of ameloblastoma encompassing about 6% of ameloblastomas. They represent cystic lesions that reveal clinical and radiographic features of a cyst, but the histopathological features demonstrate a typical ameloblastomatous epithelium lining the cyst. Plexiform unicystic ameloblastoma, a variant of unicystic ameloblastoma refers to the pattern of proliferation where one or more nodules of ameloblastomatous epithelium project from the cystic lining into the lumen demonstrating an edematous plexiform pattern. The lesion is seen more commonly in the third and fourth decades of life with less than 10% of cases being reported in the first decade. Here, we report two cases of unicystic ameloblastoma in paediatric patients. This report also aims to provide an insight on the pathogenesis and treatment aspects of this distinct entity.